Penyuluhan Perubahan Prilaku Hidup Bersih dan Sehat Masyarakat Dalam Pencegahan Covid 19 - Tauhid; Muhammad Taufiq; Adi Hidayat Argubi; Surip (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The corona virus has an impact on death continued to increase, thus providing fear, trauma and stress for the community. The Community Service Team STISIP Mbojo provides counseling and assistance in changing clean and healthy living behavior for community in Kelurahan Rabangodu Selatan. The method used is counseling and mentoring. Participants include Lurah, , RT, RW and Community. The Result obtained : First; outreach activities in providing information regarding the corona virus disease (covid) 19 epidemic and the causative factors and ways of preventing it are running smoothly. Second; assistence activities through preparing a place to wash hands in every house, encouraging the community to plan a living pharmacy in each house to create a comfortable and healthy environment, familiarize the community with wearing masks, the down movement for a clean environment, and build a harmonious spirit of mutual cooperating in togetherness to crate a healthy village , with wearing masks, the down moverment for a clean environment, and build a harmonious spirit of mutual cooperation in togetherness to create a healthy village through the clean Friday movement environment (JUMPA BERLIAN).